Prevalence and factors associated with overweight and obesity in Kenya - Rahma Mkuu; Adam Barry; Gerald Yonga; Fredrick Nafukho; Cort Wernz; Tamika Gilreath; Muhammad A.B. Chowdhury; Idethia Shevon Harvey (Preventive Medicine Reports, 2021)
Overweight and obesity rates continue to rise globally and are associated with increased chronic disease morbidity and mortality. There is evidence of high overweight and obesity prevalence in Kenya, however; a gap exists in the knowledge of national prevalence and predictors of overweight and obesity.This cross-sectional study examined data from the 2015 World Health Organization (WHO) Kenya STEPwise Survey—the first nationally representative survey to objectively measure body mass index (BMI) among Kenyan men and women. Descriptive and logistic regression analysis of 4,340 adults aged 18–69 years examined the prevalence, sociodemographic, and behavioral risk factors associated with having overweight or obesity (overweight/obesity) defined by WHOThe mean BMI was 23.51 with 31.13% having overweight/obese. The likelihood of having overweight/obesity was significantly higher among married individuals [odds ratio (OR) = 1.78, 95% confidence interval (CI) 1.19, 2.66], women (OR = 4.08, 95% CI 3.02, 5.51), urban dwellers (OR = 1.70, 95% CI 1.28, 2.25) and middle wealth or higher (OR = 2.45, 95% CI 1.91, 3.14). The likelihood of having overweight/obesity increased by age, compared to 18–29-year olds; (30–44 years (OR = 2.05 95% CI 1.50, 2.80), 45–59-year olds (OR = 2.67, 95% CI 1.97, 3.63), 60–69-year olds (OR = 3.00, 95% CI 1.99, 4.51). Adults with completed primary education or more had higher odd of having overweight/obesity (OR = 2.15, 95% CI 1.72, 2.70). compared to adults with less than primary education.Likelihood of having Overweight/obesity was highest among women, urban residents, and individuals with high education and wealth. Future studies should ascertain drivers of overweight/obesity to inform Targeted and tailored interventions and policies amongst high-risk groups.